How to Address Climate Change by Applying Novel Economic Instruments - Jan Stenis (Current Topics on Business, Economics and Finance Vol. 2, 2023)
Objectives: The Naturally Optimized Revenue Demand in Communities (NORDIC) model was employed to improve the Swedish climate by providing a practical method. Authorities, politicians, and others obtained a tool to modify the climate policy. The launched model considered and promoted the public awareness about climate change issues. Methods: The suggested methodology generated artificial shadow costs that were introduced into the public’s accounts to provide financial incentives to mitigate the climate changes. One significant factor that only by one digit expressed how effective the climate policy was over time was the associated shadow cost and its impact on the PSBR. Results: This case study showed how the climate could be improved and its fluctuations decreased by application of the NORDIC model. The findings suggested a promising approach for using economic tools to improve the climate. Conclusions: According to the study’s findings, the adaptable NORDIC model might be applied to improve the climate and reduce its danger to health. Environmental authorities and politicians who want a comprehensive tool to redesign the climate policy are potential end users. More research should be focused on developing algorithms for certain climates and affected citizens.